PENGARUH MODEL PROJECT BASED LEARNING (PjBL) BERBASIS ETNOSAINS TERHADAP AKTIVITAS DAN HASIL BELAJAR IPA PADA SISWA KELAS IX SMP PESANTREN IMMIM - Widyani; Firdaus Daud; Hartono; Muhiddin Palennari; Syamsiah (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the effect of implementing an ethnoscience-based Project-Based Learning (PjBL) model on students’ learning activities and learning outcomes. This research employed a quantitative approach with a quasi-experimental design. The research subjects consisted of two classes: an experimental class taught using the ethnoscience-based PjBL model and a control class taught using the conventional PjBL model without ethnoscience integration. The instruments used in this study included an observation sheet to assess students’ learning activities and a multiple-choice test administered before and after the treatment to measure learning outcomes. The results showed that the average score of students’ learning activities was 78.07, with a standard deviation of 9.17 and an achievement percentage of 78.07%, categorized as very active. The improvement in students’ learning outcomes in the experimental class was also higher than in the control class based on the N-gain analysis. The average pretest score was 65.66 (SD = 10.49), which increased to 86.90 (SD = 4.78) in the posttest. The N-gain value of 0.62 was classified as moderate. Inferential analysis using the t-test indicated a significant difference in both learning activities and science learning outcomes between the two classes (Sig. = 0.000). Therefore, the implementation of ethnoscience-based Project-Based Learning has a positive effect on improving students’ learning activities and science learning outcomes.